The influence of time availability, happiness, and weariness on consumers’ impulse buying tendency amidst Covid-19 partial lockdown in Malaysia - Hafizah Omar Zaki; Siti Ngayesah Ab Hamid (Penerbit Universiti Kebangsaan Malaysia, 2021)
The movement control order (MCO) and conditional movement control order (CMCO), also known as the partial lockdown imposed on Malaysian as a result of Covid-19 pandemic has affected mental health, and consumerism. Spending too much time online, feeling unhappy and weary by staying at home too long may negatively affect buying tendency during the pandemic period. A low online buying tendency may cause firms’ profits to decrease. Therefore, this study aims to examine the influence of consumers’ time availability, state of happiness, and level of weariness on their tendency to buy online during Covid-19 partial lockdown. The study uses a convenience sampling method and collected 236 responses to the survey. The data was analysed using a multiple regression. The findings highlight that time availability does not influence online impulse buying tendency, while happiness, and weariness significantly affect online impulse buying tendency. Specifically, the study found that moderate happiness and a low level of weariness influenced consumers’ tendency to buy online. The study contributes to providing insights for firms and marketers to understand consumers’ psychological states during the pandemic which could be used as a basis to develop strategies on suitable advertising medium and content.